Analisis Rasio Keuangan untuk Memprediksi Kondisi Financial Distress Perusahaan Manufaktur yang Terdaftar di Bursa Efek Jakarta - Luciana Spica Almilia; Kristijadi Kristijadi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2003)
Financial distress precedes bankruptcy. Most financial distress models actually rely on bankruptcy data, which is easier to obtain. The purpose of this research to examine financial ratios that affect financial distress condition of a firm. The sample of this research consist of 24 distress firms and 37 non-distress firms, chosen by purposive sampling. The statistic method which is used to test on the research hypothesis is logistic regression. The result show that profit margin ratio (net income/net sales), financial leverage ratio (current liabilities/total assets), liquidity ratio (current assets/current liabilities) and growth (net income/total assets growth) is a significant variable to determine of financial distress firms.Keywords: financial distress, financial ratios, bankruptcy.